â€œHillary, you have no ideaâ€: Impoliteness Strategy used as a Communicative Strategy in U.S. Presidential Debate - Panggabean, Hanna Maria (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
Impoliteness is a social phenomenon practically used to threaten someone’s face and an act of raising a conflict in the interaction. However, impoliteness is unable to reveal under politeness theory since it focuses on the constraint of verbal interaction used to save someone’s face (Mohammed & Abbas, 2015, 2016). Therefore, Culpeper (2016) suggests an impoliteness strategy to emphasize some communicative strategies used to damage the hearer’s face. One of the controversial events occurred in a presidential debate between Donald Trump and Hillary Clinton in 2016. This study explored the impoliteness strategy used by the candidates in quantitative and qualitative. This study highlighted the use of positive impoliteness as a defensive communicative strategy and negative impoliteness as an attacking communicative strategy that occurred U.S. Presidential Debate between Donald Trump and Hillary Clinton.